Danger, Crime and Rights: A Conversation between Michel Foucault and Jonathan Simon. (January 2017) - Foucault, Michel; Simon, Jonathan; Elden, Stuart
This article is a transcript of a conversation between Michel Foucault and Jonathan Simon in San Francisco in October 1983. It has never previously been published and is transcribed on the basis of a tape recording made at the time. Foucault and Simon begin with a discussion of Foucault's 1977 lecture 'About the Concept of the "Dangerous Individual" in 19th-Century Legal Psychiatry', and move to a discussion of notions of danger, psychiatric expertise in the prosecution cases, crime, responsibility and rights in the US and French legal systems. The transcription is accompanied by a brief contextualizing introduction and a retrospective comment by Simon.